The Implementation of English Online Learning Strategy at Junior High School in Rural Area Post Covid-19 Pandemic - Asmi Asmi; Munir Munir; Syarifah Farahdiba (State University of Makassar, 2023)
This study aims to (1) find out what strategy did teachers in rural area implement in their online learning post covid-19 pandemic (2) find out challenges that they faced post covid-19 pandemic and how they overcome these challenges. This study applies the qualitative method to achieve the research objectives. The subject of this study were six English teachers from junior high school that teach in rural area post covid-19 pandemic. The subjects were chosen by using purposive sampling and do not have to be large in number just following the necessity of the research. The instrument of this study is in-dept interview. The result of this study revealed that teachers in rural area applied two strategies in their online learning during the pandemic, they are online chat only and combining video conference with online chat. In addition, teachers in rural area face several challenges when implementing the online learning strategy, including poor internet connection, lack of devices (Handphone) and internet data, and lack of students’ motivation. However, teachers are able to find ways to overcome these obstacles, there are four ways, they are: limited face-to-face meeting, visiting the students, extend the submission time, and using one phone for two or several students.Keywords- online learning strategy, implementation, challenges, rural area